The Dimension of Atypical Employment in Romania - Ghinăraru, Cătălin; Mladen, Luise (Journal of Economic Development, Environment and People, 2016)
Official statistics can not always highlight the true scale of atypical work phenomenon in Romania because of the multitude of the non-standard forms of employment and because of the fact that its regulatory and monitoring mechanisms are build in accordance with the typical work model. The purpose of our research is to try to estimate the atypical employment in Romania using a variety of statistical data basis.